Ensino de precisão: um sistema para ensino de habilidades e treinamento para profissionais que atuam com pessoas autistas - Moraes, Priscilla Terumi (Universidade Federal de São Carlos, 2025)
This thesis investigates the effectiveness of Precision Teaching (PT) in training professionals working with autistic individuals. The thesis comprises four articles exploring various aspects of PT, including its implementation, efficacy in interventions with autistic individuals, the impact of graph standardization on clinical decision-making, and an online procedure for teaching the Standard Celeration Chart (SCC). Chapter 1 is introductory and explains the thesis' objectives. Chapter 2 provides a comprehensive introduction to PT, detailing its core components and offering a practical implementation guide. Chapter 3 presents a systematic literature review analyzing PT's efficacy in interventions with autistic individuals. The review included 11 studies with diverse methodological characteristics (designs, populations, skills taught). Results showed strong evidence of PT's effectiveness in academic skills (primarily mathematics and reading), along with indications of maintenance, resistance, stability, application, and generalization. The review also highlights the need for future studies with enhanced methodological rigor. Chapter 4 investigates how behavior analysts use graphs for decision-making, assessing the influence of graph standardization. In this study, 19 analysts examined 5 graphs (3 line graphs, 2 SCCs) with identical data but different scales and representations. Chapter 5 presents a study evaluating an online teaching procedure for the SCC. Four behavior analytic therapists participated, training on 18 skills using videos and online meetings. Results indicated the procedure's effectiveness in increasing correct responses and decreasing errors, with 93.4% inter-observer agreement. Results demonstrate that graph standardization improves agreement among analysts regarding instructional decisions. Finally, Chapter 6 discusses the findings, their implications for practice and research, and suggests future directions. In summary, this dissertation contributes to understanding and applying PT in interventions with autistic individuals.
Precision teaching: a system for skill instruction and training for professionals working with autistic individuals
Keywords: Ensino de precisão; Autismo; Análise do comportamento aplicada; Gráfico padrão de aceleração; Intervenção comportamental; Standard celeration chart; Behavioral intervention; Autism; CIENCIAS HUMANAS::PSICOLOGIA